Development of Corn-Oil Ester and Water Mixture Phase Change Materials for Food Refrigeration Applications. (March 2019) - Suamir, I Nyoman; Rasta, I Made; Sudirman; Tsamos, Konstantinos M.
Abstract: This research aims to investigate development of corn-oil ester and water mixtures as novel solid-liquid phase change material candidates for chilled and frozen food refrigeration applications. Thermal properties of both water and its mixture with corn-oil ester were tested by DSC and T-history methods. The results showed that corn oil could mix well in water solutions. Phase transition temperatures of the mixtures were lower than those of individual water. Corn-oil ester in the mixtures was acted as a nucleate agent and it was able to lower freezing point and to trigger ice nucleation in water which could diminish super-cooling. Addition of corn oil ester by 5% to 35% in water solutions could decrease freezing temperature from 0°C down to respectively -3.5°C to -28°C. The PCM candidates were also found to have excellent thermal properties that could fulfill requirements of thermal energy storage systems for food refrigeration applications.